Functional hemispherotomy in the treatment of drug-resistant epilepsy: a clinical case - A. A. Sufianov; R. T. Deniel; S. Zh. Stefanov; G. Z. Sufianova; A. S. Orlov; S. V. Churkin; S. I. Kostarev; S. V. Mirkhaydarov (Эпилепсия и пароксизмальные состояния, 2019)
Though brain hemiatrophy is not among the leading causes of symptomatic epilepsy; the problem remains important and is of great practical interest to neurologists and neurosurgeons in Russia. In this article; we present an example of successful surgical treatment of Dyke-Davidoff-Masson syndrome. Here; functional hemispherotomy was performed in a 22 years old female patient; as a result; the occurrence and intensity of epileptic seizures decreased. This clinical case provides hope for this procedure to show even better results if performed in early childhood.